2015
DOI: 10.1007/s40520-015-0501-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of continuous versus fractionated physical training on muscle oxidative stress parameters and calcium-handling proteins in aged rats

Abstract: Age-associated decline in skeletal muscle mass and strength is associated with oxidative stress and Ca(2+) homeostasis disturbance. Exercise should be considered a viable modality to combat aging of skeletal muscle. This study aimed to investigate whether continuous and fractionated training could be useful tools to attenuate oxidative damage and retain calcium-handling proteins. We conducted the study using 24-month-old male Wistar rats, divided into control, continuous, and fractionated groups. Animals ran a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…However, the elderly who are physically active benefit from exercise-induced adaptation in cellular antioxidant defense systems (326). Improved skeletal muscle mechanics, strength, and endurance make them less vulnerable to acute muscle injury and chronic inflammation (138).…”
Section: A Exercise As Therapymentioning
confidence: 99%
“…However, the elderly who are physically active benefit from exercise-induced adaptation in cellular antioxidant defense systems (326). Improved skeletal muscle mechanics, strength, and endurance make them less vulnerable to acute muscle injury and chronic inflammation (138).…”
Section: A Exercise As Therapymentioning
confidence: 99%
“…Kryger reported that resistance training by women at an advanced age could increase skeletal muscle mass and muscle strength [7]. More recently, the effects of habitual exercise have also been studied [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance training (RT) is the exercise strategy usually recommended to counteract age-related muscle wasting ( 6 ). Recent studies have shown that aerobic exercise training is also able to attenuate the rate of sarcopenia development ( 7 9 ). However, the precise cellular mechanisms through which resistance and aerobic training act on sarcopenia pathophysiology have not yet been fully appreciated.…”
Section: Introductionmentioning
confidence: 99%